Integrative omics analysis of plant-microbe synergies in petroleum pollution remediation - Yi-Qian Mu; Jian-Bo Song; Min Zhao; Peng Ren; Han-Yu Liu; Xuan Huang (PeerJ)
As the petrochemical industry continues to advance, the exacerbation of ecological imbalance and environmental degradation due to petroleum pollution is increasingly pronounced. The synergistic interaction between plants and microorganisms are pivotal in the degradation of petroleum hydrocarbons; however, the underlying degradation mechanisms are not yet fully understood. This study aims to contribute to understanding these mechanisms by employing a multi-omics approach, integrating transcriptomics, 16S rRNA gene sequencing, and metabolomics, to analyze key differential genes, dominant microbial strains, and root-secreted metabolites involved in petroleum hydrocarbon degradation in alfalfa. Our findings revealed that several stress-related genes are upregulated in alfalfa contaminated with petroleum hydrocarbon. Moreover, Pseudomonas, Rhodococcus, and Brevundimonas were identified as dominant species in the rhizosphere microbiome. Metabolomics analysis identified pantothenic acid, malic acid, and ascorbic acid as critical metabolites that enhance hydrocarbon degradation. Application of pantothenic acid in oil-contaminated soil increased the degradation rate by approximately 10% compared to other treatments. These results highlight the potential of alfalfa-based phytoremediation strategies and offer a novel perspective for improving the efficiency of soil decontamination. Further research is needed to validate the scalability of these strategies for practical applications.